Down and out : poverty and exclusion in Australia - Saunders, Peter, 1948- (Studies in poverty, inequality, and social exclusion., 2011)
Drawing on the author's extensive research expertise and his links with welfare practitioners, this landmark study provides the first comprehensive assessment of the nature and associations between the three main forms of social disadvantage in Australia: poverty, deprivation and social exclusion.